Improving Reading Comprehension Through the Scaffolded Reading Experience (SRE) Strategy for Tenth-Grade Students at SMK Negeri 1 Dampal Selatan - Sitti Hawaena; Rahmatul Ummu Arifin; Nahdawati; Meli; Wilna Ahmad (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This research aimed to determine whether the implementation of the Scaffolded Reading Experience (SRE) strategy could improve the reading comprehension of tenth-grade students at SMK Negeri 1 Dampal Selatan. The main problems faced by the students were their difficulty in understanding English reading texts and their lack of attention to punctuation while reading. These problems affected their confidence and comprehension during reading activities. Therefore, the researcher implemented the Scaffolded Reading Experience (SRE) strategy to help students pay more attention to punctuation and understand the content of English reading texts more effectively. This research used a quantitative method with a quasi-experimental design. The subjects of the research were two classes: class X TKJ A as the experimental class, consisting of 22 students, and class X TKJ B as the control class, consisting of 20 students. Before the treatment was conducted, both classes were given a pre-test to measure their initial reading comprehension. The treatment was carried out in eight meetings using reading texts. After the treatment, a post-test was administered to measure the students’ improvement. The data were analyzed using a paired-sample t-test through the SPSS program. The results showed that the mean score of the experimental class increased from 54.17 to 65.70, while the mean score of the control class increased from 49.67 to 60.37. The t-test value was 2.364, which was higher than the t-table value of 2.021. This indicated that the null hypothesis was rejected and the alternative hypothesis was accepted. Therefore, it can be concluded that the Scaffolded Reading Experience (SRE) strategy was effective in improving students’ reading comprehension at SMK Negeri 1 Dampal Selatan.